Septic embolism: the importance of an adequate clinical approach: a case report, Bogota, Colombia (2016)
Neurological complications of infectious endocarditis have a high prevalence globally and its clinical presentation remains a clinical challenge. A previously healthy 36-year old male presented at the emergency room with persistent fever and headache. The patient was referred to Neurology section after initial diagnostics and treatment. They detected abnormal skin lesions and cardiac murmur. Based on the presentation and abnormal physical examination findings, their impression was an embolic process with infectious etiology prompting medical treatment. Patient was concomitantly referred to Cardiology section and infective endocarditis was confirmed by echocardiogram. Cranial Magnetic Resonance Imaging (MRI) confirmed an ischemic embolic process. Successful surgical treatment followed. This highlights the importance of good clinical history and physical examination as the cornerstone of diagnosis, even for the clinically challenging cases. Good clinical approach and appropriate use of imaging technology greatly benefited the patient by allowing early diagnosis and treatment hence prevention of further complications.